CORRUPTION, YOUTH, INTERNET AND … ARMY - Nisnevich, Yuliy A. (European Scientific Journal, ESJ, 2014)
In this paper there is analysis of motives, wheels and conditions that led to a wave of mass protests against authoritarian rulers in Arab states of Near East and Maghreb. It is shown that corruption in the state power system served as the main incentive for mass protests, and their major wheel was represented by the youth as the most educated, informed and oriented at postindustrial development models part of society. Social networks based both on postindustrial technologies, and on the traditional for the Arab world “technique” of a Friday prayer became an organizational and communication ground. Position of the army serves as a factor influencing “toughness” and duration of resistance in a determinative way. This study was carried out within “The National Research University Higher School of Economicsʼ Academic Fund Program in 2013-2014, research grant №12-01-0150”.